Physicochemical properties, antimicrobial activity, and contaminants in personal care products from Bangladesh - Samiha, Zeba; Joya, Sherajom Moniroh; Sultana, Saima; Islam, Md. Mazharul; Shoeb, Mohammad; Reza, Md. Shahed (Current Research on Biosciences and Biotechnology, 2025)
Personal care products help maintain hygiene and appearance by cleansing and protecting the skin and hair, supporting overall health and barrier function. The research was aimed at evaluating the quality of different locally available skin care products. This study assessed the physicochemical properties, antimicrobial activity, and the presence of Na+ and K+ ions in various personal care products (PCPs), including face washes, shower gels, and shampoos available in Dhaka, Bangladesh. It also evaluated the total active ingredient content, saponification, acid, and iodine values, the presence of plastic microbeads, and heavy metals such as lead (Pb) and cadmium (Cd). Antibacterial susceptibility tests against Escherichia coli (E. coli) and Staphylococcus aureus (S. aureus) were conducted using the Agar Diffusion Method. Na+ and K+ ions were quantified using a flame photometer. Active ingredient levels, saponification, acid, and iodine values were determined through titrimetric methods. The shapes of plastic microbeads were examined with a stereo-microscope, and their composition was analyzed spectrophotometrically. Heavy metals were measured using atomic absorption spectrometry (AAS). The pH of the samples ranged from 4.62 to 10.23. Shampoos exhibited the highest antimicrobial activity, while face washes were the least effective. Na+ concentrations varied from 49.45 to 218.74 mgL-1, and K+ levels ranged from 1.3 to 125.60 mgL-1. Saponification values were in between 160.0 and 700.0 mgg-1, and acid values ranged from 0.9 to 11.0 mgg-1. Microbeads were either spherical or irregular, composed mainly of polyamide, polyethylene, and polyester. Lead concentrations varied between 0.75 and 7.54 mgL-1, with face washes containing high levels. Cadmium was below detection limits. The study highlights the need for careful selection of PCPs, considering their potential adverse effects on skin health and hygiene.